FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN JUMLAH KOLONI BAKTERI DAN KEBERADAAN E. coli PADA AIR CUCIAN PERALATAN MAKAN PEDAGANG MAKANAN DI TEMBALANG - Rifka Fuazia Bilqis; Nur Endah Wahyuningsih; Yusniar Hanani Darundiati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The dirty washing water can contaminate the utensil and spoil the quality of the food and causing food borne diseases. The Regulation of Ministry of Health no. 1908 year of 2003 mentions that the washing water used to wash utensils should not contain germ counted >100 colonies/ml and it should not contain E. coli. This study aimed to determine the factors related to the number of colonies of bacteria and E. coli in the washing water for utensil of food vendors at Tembalang. The study was observational, with cross sectional study design. Study subjects were 46 food vendors. There was a significant relation between the handling of washing dishes (p=0.022) with the presence of E. coli in the washing water of utensil. There was no significant relation between the physical condition of the source of water (p=1.000), the handling of washing dishes (p=0.543), personal hygiene condition handlers (p=1.000), and the type of washing water used to clean the utensil (p=1.000) with the number of colonies of bacteria in the washing water. There was no significant relation between the physical condition of the source of water (p=0.247), condition handlers personal hygiene (p=0.900), and types of water used to wash the utensil (p=0.247) with the presence of E. coli in the washing water of utensil. It can be concluded that the microbiological quality of washing water used by food vendors at Tembalang was not that good. It is necessary to have socialization and improvement of food sanitation hygiene practices to the society.